Pelaksanaan Upacara Yadnya Sebagai Implementasi Peningkatan Dan Pengamalan Nilai Ajaran Agama Hindu - I Ketut Wartayasa (Kamaya: Jurnal Ilmu Agama, 2018)
Hindus in Bali are religious people, we can see this from the activities of daily life that always puts the element of God's power as an estuary consequence of responsibility, this can be proven from religious routines through the implementation of the yad ceremony as a form of devotional service before Ida Sang Hyang Widhi Wasa. The background of the emergence of yad is because of the identification that God Almighty is the master of all yadnya then there arises the awareness that humans must carry out yadnya because yadnya is the law of universality that cannot be avoided by humans.